Calculation of the Level of Death Risk in Traffic Accidents Based On Aggregate Loss Costs - Audina, Maudy Afifah; Hasanah, Anggraeni Mafhul (Indonesian Operations Research Association (IORA), 2024)
The transportation sector is undergoing transformative changes, driven by the emergence of autonomous vehicles and advancements in smart transportation systems. However, these innovations pose novel challenges, particularly in mitigating the risk of fatalities in traffic accidents. This study focuses on estimating death risk in traffic accidents by analyzing aggregate loss costs within the context of traffic safety. Employing a quantitative approach, the research utilizes the Poisson distribution to model the frequency of fatal incidents and the exponential distribution function to depict the distribution of associated losses. The study's objective is to calculate aggregate losses, offering insights into the potential severity of risks. Through a comprehensive analysis, the results affirm the efficacy of the Poisson and exponential distributions in assessing death risk in traffic accidents, with the highest estimated aggregate loss cost reaching Rp3.734.832,09.Â